PROFUNDIDADE DE PLANTIO E PADRÃO DE TOLETE NA PRODUTIVIDADE DE CANA -DE -AÇÚCAR - Stasiak, Maurício; Kruger, Cleusa A. M. B.; Silva, José A. G. d.; Quadros, Valmir J. d.; Melo, Elder D.; Silva, Adair J. d.; Kalb, Marcos; Santos, Cleverson D. d.; Wagner, Juliano F.; Viera, Rogério (Salão do Conhecimento, 2013)
Resumo